Analisis Framing Pemberitaan Tragedi Kanjuruhan Malang pada Media Online Detik.com dan Kompas.com - Prathama Artha, Alan; Ismandianto, Ismandianto (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
This study aims to analyze the media framing of Detik.com and Kompas.com regarding the Kanjuruhan football riot tragedy in Malang at the end of 2022, with a focus on identifying the framing and media ideologies reflected in online reporting. The research employs the approach of the theory of social reality construction, with data collection through observation, documentation, and a literature review of 20 news articles covering the period from October 2 to October 14, 2022. The research findings reveal that Detik.com emphasizes framing news around the victims, attempting to convey empathy for them, and its reporting tends to be brief and less in-depth. On the other hand, Kompas.com is more oriented toward the development of events and problem resolution, with more informative and comprehensive reporting. The media ideology of Detik.com is more pronounced in its focus on the perspectives of the victims and the quantity of reporting, whereas Kompas.com emphasizes the development of issues and the government's role in resolving the case, with reporting focused on facts and data.